Factors influencing household and women's dietary diversity in migrant households in central Nepal - Gartaula, Hom Nath; Atreya, Kishor; Kattel, Kanchan; Rahut, Dil Bahadur (2024)
Food security and dietary diversity, defined as providing either physical (availability) or economic (accessibility) access to food, are linked with access to and control over productive resources and is a highly-gendered phenomenon. In Nepal, labor out-migration has increased household income and may have increased people’s ability to access diverse food either by increasing investment in agriculture or purchasing various food items from the market. However, the relationship between household dietary improvement and labor out-migration is complex. Drawing on a survey of 1,053 migrant households in three agroecological regions of Nepal, this paper disentangles this complex phenomenon by showing how household dietary diversity and women’s dietary diversity are influenced by biophysical, social, economic, and cultural factors. The influence of the amount of remittances, land abandonment, and women confined to the house by household chores are some factors that policy makers should consider seriously in designing gender-sensitive nutrition policies. The expansion of women’s agency contributes to enhancing dietary diversity and specifically women’s dietary diversity at the household level; however, how these factors determine an individual’s dietary diversity depends on intrahousehold dynamics and relations.